MNEs’ location strategies and labor standards: The role of operating and reputational considerations across industries - Maggioni, Daniela; Santangelo, Grazia D.; Koymen-Ozer, Seda (Journal of International Business Studies, 2019)
We investigate the role of local labor standards on MNEs’ location decisions across different sectors and sub-national regions within a developing country. We suggest that foreign investors adopt selective location strategies in connection with specific labor standards as a result of reputational and operating considerations. Foreign firms in more hazardous sectors prefer locations with higher occupational health and safety standards because they are more exposed to reputational risks. Those in sectors with less reversible investments prefer locations with lower degrees of unionization because their lower bargaining power increases their sensitivity to operating costs. We test our arguments across 26 sub-national Turkish regions over the period 2005–2011.